The addition of calcium oxide with different doses in the recirculation system to improve the abalone Haliotis squamata seed production - Eddy Supriyono; Debora Victoria Liubana; Tatag Budiardi; Irzal Effendi (Jurnal Akuakultur Indonesia)
Information about abalone growth is necessary to overcome the abalone culture sustainability. Water quality parameters are aspects that need to be reviewed, one of which is the calcium level in the water. The aim of this study was to determine the optimal calcium dose in recirculation system for abalone (Haliotis squamata) growth. The study was conducted with an experimental method with four treatments (calcium oxide with doses of 0, 15, 30, 45 mg/L) and three times replications. Abalone with 2.3 g body weight, 2.3 cm shell length, and 1.2 cm shell width was reared for 60 days in recirculation system and fed with Gracilaria verrucosa. The results showed that the best abalone treatment medium with the addition of calcium oxide to increase the abalone seed production was 15 mg/L CaO with 100% survival rate, 31.57±2.82% feed efficiency, and 0.56±0.06%/day specific growth rate.